Optimization of spect for parathyroid imaging with varying instrumentation parameters: A simulation study - Oral, Ayşegül. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
Parathyroid problems are frequently experienced problems. Nuclear medicine has a signi cant role in determining the treatment. The study tried to nd out the visibility of the small adenoma with a simulation method and the usefulness of the simulation with changing optimal instrumentation and reconstruction parameters for parathyroid SPECT imaging. In previous studies, parathyroid SPECT Imaging has been optimized using physical phantoms only. In this study, an anthropomorphic phantom (Zubal Phantom) and a sphere as a parathyroid adenoma were simulated. Simulated adenoma was chosen small (0.58 cm3). In order to create a parathyroid adenoma SPECT image, 99mTc-Sestamibi SPECT was used.SPECT acquisitions were done simulating two separate SPECT devices and di erent types of parallel hole collimators.It was found that the optimal parameters were LEUHR collimator, 16 iterations and no scatter correction for Siemens Symbia gamma camera (CNR:3.74). LEHR collimator, 16 iterations, without scatter correction gave better result according to the other parameters for General Electric In nia gamma camera (CNR:2.81). Scatter correction did not result in a signi cant improvement in this study. The study showed that a small parathyroid adenoma could be studied with computer simulation methods. The optimal parameters could be investigated without the necessity of the machine itself. With this exibility, optimal parameters for each camera could be studied in a shorter time in comparison with using real SPECT devices.|Keywords : Parathyroid, SPECT, Collimator, Optimization, Simulation.
Keywords: Parathyroid glands.